(untitled) (Revista Apotheke, 2026)
This article reflects on the ongoing artistic process developed within the research project Kairos Babel, part of the PhD in Painting at the Faculty of Fine Arts, University of Lisbon. Centered on pictorial practice, the study approaches the studio as a territory of listening and chromatic thought, where gesture, color, and material intertwine as modes of knowledge. Based on the empirical observation of the workspace-considered both a physical site and a conceptual device-the research examines how the chromatic, material, and symbolic conditions of the studio influence image construction and perceptual experience. Drawing on theoretical references such as Josef Albers, Norman Bryson, Barbara Bolt, and Maurice Merleau-Ponty, the reflection proposes the studio as a performative field of learning, where knowledge emerges through action, experimentation, and error. The text further analyzes the use of pink as a chromatic and symbolic axis, relating it to the concepts of poiesis, “non-place,” and symbolic reinscription. It argues that pictorial practice, by interweaving experience, memory, matter, and color, constitutes a form of situated visual thinking and a process of identity reinscription.